CNSC-17. GLIOMA SYNAPSES RECRUIT MECHANISMS OF ADAPTIVE PLASTICITY. (14th November 2022) - Taylor, Kathryn; Barron, Tara; Zhang, Helena; Hui, Alexa; Hartmann, Griffin; Ni, Lijun; Venkatesh, Humsa; Du, Peter; Mancusi, Rebecca; Yalçin, Belgin; Chau, Isabelle; Ponnuswami, Anitha; et al.
Abstract: The nervous system plays an increasingly appreciated role in the regulation of cancer. In malignant gliomas, neuronal activity drives tumor progression not only through paracrine signaling factors such as neuroligin-3 and brain-derived neurotrophic factor (BDNF), but also through electrophysiologically functional neuron-to-glioma synapses. Malignant synapses are mediated by calcium-permeable AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid) receptors in both pediatric and adult high-grade gliomas, and consequent depolarization of the glioma cell membrane drives tumor proliferation. The nervous system exhibits plasticity of both synaptic connectivity and synaptic strength, contributing to neural circuit form and functions. In health, one factor that promotes plasticity of synaptic connectivity and strength is activity-regulated secretion of the neurotrophin BDNF. Here, we show that malignant synapses exhibit similar plasticity regulated by BDNF-TrkB (tropomyosin receptor kinase B) signaling. Signaling through the receptor TrkB, BDNF promotes AMPA receptor trafficking to the glioma cell membrane, resulting in increased amplitude of glutamate-evoked currents in the malignant cells. This potentiation of malignant synaptic strength shares mechanistic features with the long-term potentiation (LTP) that is thought to contribute to memory and learning in the healthy brain. BDNF-TrkB signaling also regulates the number of neuron-to-glioma synapses. Abrogation of activity-regulated BDNF secretion from the brain microenvironment or loss of TrkB in human glioma cells exerts growth inhibitory effects in vivo and in neuron:glioma co-cultures that cannot be explained by classical growth factor signaling alone. Blocking TrkB genetically or pharmacologically abrogates these effects of BDNF on glioma synapses and substantially prolongs survival in xenograft models of pediatric glioblastoma and diffuse intrinsic pontine glioma (DIPG). Taken together, these findings indicate that BDNF-TrkB signaling promotes malignant synaptic plasticity and augments tumor progression. While targeting Trk signaling is presently being explored for NTRK-fusion brain tumors, these findings indicate that BDNF-TrkB signaling may also represent an important therapeutic target for NTRK2 wildtype gliomas.